Rekonstrusi Regulasi Harta Bersama Dalam Perkawinan Berbasis Nilai Keadilan Gender - Sridepi, Sridepi; Nurcahaya, Nurcahaya (JAWI : Journal of Ahkam Wa Iqtishad, 2024)
This study, titled “Reconstruction of Joint Asset Regulations in Marriage Based on Gender Equity Values,” aims to reevaluate and redefine the management and distribution of joint assets in marriage to align more closely with principles of gender equity. Within Indonesian legal frameworks, joint assets are typically governed by principles that may still need refinement to ensure fair and balanced treatment for both spouses. Ideally, marriage laws should acknowledge asset rights not only from a legal perspective but also by incorporating gender equity values that promote equal rights and shared responsibilities between husbands and wives. The study employs a descriptive qualitative approach through library research, gathering data by examining legal texts such as laws, books, journals, and relevant legal documents. This approach enables the researcher to gain a comprehensive understanding of the current regulations on joint assets and to explore ways in which gender equity values could inform regulatory adjustments. The findings of this study are expected to offer recommendations for legislative frameworks on joint assets that prioritize not only legal entitlements but also equitable gender rights. This proposed reconstruction of joint asset regulations aims to establish a fairer legal foundation for marriage, fostering a marital system that supports gender equality and has a positive impact on both family life and society.